2017
DOI: 10.1074/jbc.m117.817452
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione limits aquacopper(I) to sub-femtomolar concentrations through cooperative assembly of a tetranuclear cluster

Abstract: The tripeptide glutathione (GSH) is a crucial intracellular reductant and radical scavenger, but it may also coordinate the soft Cu(I) cation and thereby yield pro-oxidant species. The GSH-Cu(I) interaction is thus a key consideration for both redox and copper homeostasis in cells. However, even after nearly four decades of investigation, the nature and stability of the GSH-Cu(I) complexes formed under biologically relevant conditions remain controversial. Here, we revealed the unexpected predominance of a tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
102
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(109 citation statements)
references
References 46 publications
7
102
0
Order By: Relevance
“…Forschungsartikel mainly Cu I 4 -MT was formed after 4hours incubation, depending on the copper complex, contributions of other Cu I 4 -MT dependent complexes (such as ternary complexes of Cu I 4 -MT with GSH and/or ligands) were observed upon mixing. [16,18] Concerning the stability of the studied copper complexes against copper transfer to cytosolic-relevant concentrations of GSH and Zn 7 -MT,t he following observations can be made: i) Cu I -(BCS) 2 complex dissociates within the mixing-time and Cu I binds to MT.B CS and derivatives are some of the strongest Cu I chelators used in biology.H owever,a t1 0mm concentration, the complex is not thermodynamically stable enough to resist to Cu I transfer to MT.Ahigher concentration of hundreds of mm BCS would be needed to compete for Cu I with MT.H owever, such high concentrations are difficult to reach and less relevant from ad rug point of view.i i) Cu II -(Phen) 2 and Cu II -(5,5'-DmBipy) 2 also dissociate within mixing-time.T his is in line with their very fast reduction to Cu I -(Phen) 2 and Cu I -(5,5'-DmBipy) 2 and with the lower thermodynamic stability of the Cu I -complexes compared to Cu I -MT complex (logb 2 [Cu I -(Phen) 2 ] = 15.8). [27] Thus,C u II -(Phen) 2 and Cu II -(5,5'-DmBipy) 2 are rapidly reduced and Cu I is immediately transferred to MT.iii)Dissociation by reduction of Cu II -Dp44mT,C u II -gtsm, and Cu II -(APDTC) 2 is slower compared to Cu II -(Phen) 2 and Cu II -(5,5'-DmBipy) 2, with t 1/2 of approximately 4, 50, and 20 min, respectively (Table 1).…”
Section: Angewandte Chemiementioning
confidence: 99%
See 1 more Smart Citation
“…Forschungsartikel mainly Cu I 4 -MT was formed after 4hours incubation, depending on the copper complex, contributions of other Cu I 4 -MT dependent complexes (such as ternary complexes of Cu I 4 -MT with GSH and/or ligands) were observed upon mixing. [16,18] Concerning the stability of the studied copper complexes against copper transfer to cytosolic-relevant concentrations of GSH and Zn 7 -MT,t he following observations can be made: i) Cu I -(BCS) 2 complex dissociates within the mixing-time and Cu I binds to MT.B CS and derivatives are some of the strongest Cu I chelators used in biology.H owever,a t1 0mm concentration, the complex is not thermodynamically stable enough to resist to Cu I transfer to MT.Ahigher concentration of hundreds of mm BCS would be needed to compete for Cu I with MT.H owever, such high concentrations are difficult to reach and less relevant from ad rug point of view.i i) Cu II -(Phen) 2 and Cu II -(5,5'-DmBipy) 2 also dissociate within mixing-time.T his is in line with their very fast reduction to Cu I -(Phen) 2 and Cu I -(5,5'-DmBipy) 2 and with the lower thermodynamic stability of the Cu I -complexes compared to Cu I -MT complex (logb 2 [Cu I -(Phen) 2 ] = 15.8). [27] Thus,C u II -(Phen) 2 and Cu II -(5,5'-DmBipy) 2 are rapidly reduced and Cu I is immediately transferred to MT.iii)Dissociation by reduction of Cu II -Dp44mT,C u II -gtsm, and Cu II -(APDTC) 2 is slower compared to Cu II -(Phen) 2 and Cu II -(5,5'-DmBipy) 2, with t 1/2 of approximately 4, 50, and 20 min, respectively (Table 1).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[17] GSH can bind Cu I quite strongly (logK % 17) forming multinuclear clusters Cu I x -GSH y ,b ut under normal physiological conditions,asteady-state complex with Cu I is unlikely. [18] However,i tc an have an important impact as aC u II reducing agent. [19] Indeed, our previous studies revealed that the GSH/MT system can efficiently abstract copper from Cu II -amyloid-b and Cu II -thiosemicarbazone complexes by Cu II reduction and Cu I transfer to MT.…”
Section: Introductionmentioning
confidence: 99%
“…This labile pool is regulated through a complex interplay between cytosolic metallochaperones, membrane-localized transporters, and storage proteins such as metallothionein. [1] Inferring from recent affinity measurements of endogenous Cu I ligands, [2] labile cellular Cu I is buffered at attomolar levels or below. Despite such exceptional binding affinities, the transfer of Cu I between chaperones and transport proteins occurs with rapid kinetics, [3] likely involving an associative exchange mediated through specific protein-protein interactions.…”
mentioning
confidence: 99%
“…For example, mixed amine-thioether donors, which have been frequently employed for the construction of Cu I -selective fluorescent probes, [5] offer only dissociation constants in the pico- to femtomolar range. While bathocuproine disulfonate (BCS) [6] has been successfully utilized to characterize cuproproteins with attomolar dissociation constants, [2b] as a bidentate ligand it must be employed at significant excess over Cu I and in some cases ternary complex formation has been reported. [6–7] Synthetic ligands with sub-attomolar dissociation constants have been realized by mimicking the thiolate coordination environment of Cu I proteins; [8] however, thiolates may also bind to other biologically relevant metal cations such as Zn II or Fe II and are sensitive to pH and thiol-disulfide redox status, both of which may vary with the cellular microenvironment.…”
mentioning
confidence: 99%
“…[95] The major speciesf ormed by Cu I and GSH is at etranuclear [Cu 4 (GS) 6 ]c luster, also presumed to have astructure similarto[ Cu 4 (SPh) 6 ] 2À . [96] The structural diversity of Cu I -Cys chemistry is further demonstrated by crystal structureso ft he Atx1 family of cytosolic Cu I metallochaperones. These proteins uset he thiolates from a CXXC motif to tightly bind [77,78,91,97] as ingle, solvent exposed and coordinatively unsaturated, Cu I ion that can be readily transferred by ligand exchange.…”
Section: Copper Clusters In Other Systemsmentioning
confidence: 99%